Does climatic variation drive the adjustment of functional traits? An assessment of Tropical Montane Cloud Forest tree species - Andrés-Hernández, Agustina Rosa; Rodríguez-Ramírez, Ernesto C. (Frontiers in Plant Science, 2025)
IntroductionTropical montane cloud forests (TMCFs) host specialized plant species reliant on persistent atmospheric humidity, including fog immersion obligates and relict assemblages. Understanding anatomical and morphological adaptations in TMCF woody angiosperms is critical for elucidating their acclimation strategies to hydric stress under shifting fog regimes. This study investigates interspecific variability in wood and leaf traits among 10 TMCF tree species in Mexico’s Medio Monte Natural Protected Area, hypothesizing that distinct anatomical strategies emerge in response to climatic stressors.MethodsWood anatomical (e.g., vessel density, hydraulic diameter, fiber length) and leaf morphological traits (e.g., lamina length, vein density, leaf organization) were analyzed across species. Traits were correlated with climatic variables—mean maximum/minimum temperatures, monthly precipitation, and evapotranspiration—to identify adaptive patterns. Statistical analyses quantified interspecific differences and assessed trait-climate relationships.ResultsSignificant interspecific divergence occurred in both wood and leaf traits. Wood anatomy was strongly influenced by mean maximum temperature, precipitation, and evapotranspiration, affecting vessel density, vulnerability index, ray dimensions, and fiber length. Leaf traits correlated with temperature extremes and evapotranspiration, driving variation in leaf size, apex/base morphology, venation complexity, and marginal teeth. Notably, hydraulic efficiency (e.g., wider vessels) aligned with higher precipitation, while drought-associated traits (e.g., denser veins) linked to elevated temperatures.DiscussionTMCF species exhibit trait-based strategies balancing hydraulic safety and efficiency, reflecting niche partitioning under microclimatic gradients. Temperature and water availability differentially shape wood and leaf adaptations, with vessel architecture and venation patterns acting as key regulators of water loss. These findings underscore the functional diversity of TMCF trees and their capacity to acclimate to environmental variability. Conservation efforts must prioritize microclimate preservation to safeguard these adaptive traits amid climate change.